Membrane fouling and wetting in membrane distillation and their mitigation by novel membranes with special wettability. (1st April 2017) - Wang, Zhangxin; Lin, Shihong
Abstract: Membrane distillation (MD) has been identified as a promising technology to desalinate the hypersaline wastewaters from fracking and other industries. However, conventional hydrophobic MD membranes are highly susceptible to fouling and/or wetting by the hydrophobic and/or amphiphilic constituents in these wastewaters of complex compositions. This study systematically investigates the impact of the surface wetting properties on the membrane wetting and/or fouling behaviors in MD. Specifically, we compare the wetting and fouling resistance of three types of membranes of different wetting properties, including hydrophobic and omniphobic membranes as well as composite membranes with a hydrophobic substrate and a superhydrophilic top surface. We challenged the MD membranes with hypersaline feed solutions that contained a relatively high concentration of crude oil with and without added synthetic surfactants, Triton X-100. We found that the composite membranes with superhydrophilic top surface were robustly resistant to oil fouling in the absence of Triton X-100, but were subject to pore wetting in the presence of Triton X-100. On the other hand, the omniphobic membranes were easily fouled by oil-in-water emulsion without Triton X-100, but successfully sustained stable MD performance with Triton X-100 stabilized oil-in-water emulsion as the feed solution. In contrast, the conventional hydrophobic membranes failed readily regardless whether Triton X-100 was present, although via different mechanisms. These findings are corroborated by contact angle measures as well as oil-probe force spectroscopy. This study provides a holistic picture regarding how a hydrophobic membrane fails in MD and how we can leverage membranes with special wettability to prevent membrane failure in MD operations. Graphical abstract: Highlights: Hydrophobic MD membranes are subject to oil fouling and surfactant wetting. Omniphobic MD membranes resist surfactant wetting but not oil fouling. Composite MD membranes resist surfactant fouling but not oil wetting. The performance of a membrane strongly depends on the feed composition.